A five-Primary photostimulator suitable for studying intrinsically photosensitive retinal ganglion cell functions in humans - Cao, Dingcai (2015)
Intrinsically photosensitive retinal ganglion cells (ipRGCs) can respond to light directly through self-contained photopigment, melanopsin. IpRGCs also receive inputs from rods and cones. Thus, studying ipRGC functions requires a novel photostimulating method that can account for all of the photoreceptor inputs. Here, we introduce an inexpensive LED-based five-primary photostimulator that can control the excitations of rods, S-, M-, L-cones and melanopsin-containing ipRGCs in humans at constant background photoreceptor excitation levels, a critical requirement for studying the adaptation behavior of ipRGCs with rod, cone or melanopsin input. We describe the theory and technical aspects (including optics, electronics, software and calibration) of the five-primary photostimulator. Then we present two preliminary studies using the photostimulator we have implemented to measure melanopsin-mediated pupil responses and temporal contrast sensitivity function (TCSF). The results showed that the S-cone input to pupil responses was antagonistic to the L-, M- or melanopsin inputs, consistent with an S-OFF and (L+M)-ON response property of primate ipRGCs (Dacey et al., 2005). In addition, the melanopsin-mediated TCSF had a distinctive pattern compared with L+M or S-cone mediated TCSF. Other than control individual photoreceptor excitation independently, the five-primary photostimulator has the flexibility in presenting stimuli modulating any combination of photoreceptor excitations, which allows to study the mechanisms by which ipRGCs combine various photoreceptor inputs.